Correction: Inter- and intradialytic fluid volume changes and vascular stiffness parameters in patients on hemodialysis. - Aya Lafta; Judy Ukrainetz; Sara Davison; Stephanie Thompson; Aminu Bello; Branko Braam (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0262519.].